2007 IEEE International Symposium on Industrial Electronics 2007
DOI: 10.1109/isie.2007.4375023
|View full text |Cite
|
Sign up to set email alerts
|

CO-tolerant operation of platinum-loaded PEM fuel cells

Abstract: Abstract-Biomass is a green energy source, which can be converted to hydrogen rich gas. If this gas is used as feedstock for a PEM fuel cell, it is possible to convert biomass to electricity in an environmental friendly way. A disadvantage of a PEM fuel cell is that platinum, which is used as catalyst to speed up the anode reaction, is a good adsorbent for CO. Carbon monoxide will adhere to the platinum surface blocking the catalyst for hydrogen oxidation. In order to clean the catalyst, oxygen can be added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The electrical position of the individual cells in the stack determined their CO-tolerance and regeneration. 197 Other advantages found by Mao et al (2000) were the rapid and more controllable application of this pulsing technique compared to oxidant bleeding. 198…”
Section: Negative Potential Pulsesmentioning
confidence: 97%
See 1 more Smart Citation
“…The electrical position of the individual cells in the stack determined their CO-tolerance and regeneration. 197 Other advantages found by Mao et al (2000) were the rapid and more controllable application of this pulsing technique compared to oxidant bleeding. 198…”
Section: Negative Potential Pulsesmentioning
confidence: 97%
“…Wingelaar et al (2007) studied the application of periodic negative voltages to regenerate a system composed of four cells fed in series, but electrically connected in pairs (the first two and the last two in parallel). 197 Although the application of negative voltage pulses requires a significant amount of power, it was possible to increase to up to 500% the voltage output of the system when exposed to 50 ppm CO/H2. The electrical position of the individual cells in the stack determined their CO-tolerance and regeneration.…”
Section: Negative Potential Pulsesmentioning
confidence: 99%
“…A drawback of this method is that the produced fuel is not pure and contains by-products of the process such as carbon monoxide (CO), which can be as high as 500 ppm during reformer starting process. This poses an additional issue to the operation of PEM stacks, since it has been shown that the use of CO contaminated fuel degrades the performance of the fuel cell in terms of output voltage and power due to poisoning of the platinum catalyst contained in its membrane [7,8].…”
Section: Introductionmentioning
confidence: 99%